(untitled) (International Journal of Engineering and Computer Science, 2017)
With the advent growth of sensitive information on cloud ,Cloud security is getting more important than even before. Cloud computing is a type of computing that relies on sharing computing resources rather than having local server, or personal devices to handle applications. The cloud computing aim to providing IT as a service to the cloud user on demand basis with greater flexibility, availability ,and reliability, with utility computing model. Millions of users, use a cloud computing for various purpose, therefore security, integrity, authentication privacy and confidentiality on the cloud is a major concern.To address this issue, cryptographic algorithm are use to protect the private data over the cloud. The two type of algorithm is highly used in cryptography are symmetric and asymmetric for encrypting and decrypting the text .As if data used through internet is highly confidential which are not public viewing. so ,this work focuses on providing security to a data on cloud using elliptic curve cryptographic algorithm. This algorithm raises the confidentiality level to an exceptionally high standard using minimum resources as compared to other existing algorithms like RSA, DES, AES etc .The another major concern on cloud computing is to maintain the integrity of data stored on the cloud. Cloud server have multiple users and owners data which can be attacked or modified by outside attackers. Therefore, a new concept is added which check the data Integrity on both the module data admin and data user. This entity called data verifier. It consist of four entities data admin, cloud server ,data Verifier and data user. Data verifier perform main role of data integrity check at both the side of data owner as well as data user. It verifies the integrity of data on demand of the data owner while data owner want to verify its own uploaded data on cloud ,so that it verify whether the data uploaded on cloud is tampered or not .where as data user can check integrity after downloading the text file which is share by data owners .This verifier scheme make use of SHA-1 Hash key algorithm for integrity check.